Discover national monuments, national parks, natural wonders - Brown, Cynthia L. (Cynthia Light) (Discover your world series., 2008)
Fascinating facts about America's most popular natural landmarks provide the backbone for this collection of activities that replicate the organic processes that formed them. Interspersed with history, factoids, and sidebars, this engaging reference explores scientific concepts, such as the formation of coral reefs and the cause of volcanic eruptions. Each monument--from the Lava Beds to the Petrified Forest--is showcased in a graphic multipage spread and is followed by hands-on experiments, allowing children to make their own stalactites and discover how a river can erode rock into a canyon. Expressing true appreciation for the United States' natural wonders, this comprehensive guide clearly illustrates their formation, from glittering caves to giant trees.